Giant leiomyosarcoma of the anterior abdominal wall: case report and review of the literature - Sanchez, Yankel; Altamirano, Karla; Garcia, Manuel (International Journal of Research in Medical Sciences, 2022)
Smooth muscle tumors are rare tumors with a low worldwide incidence, which is a diagnostic and therapeutic challenge for doctors, within these, leiomyosarcomas are tumors that occur more frequently in the uterus or abdominal cavity, however, another presentation called leiomyosarcomas peripheral which are subdivided into cutaneous or subcutaneous which tend to appear in the extremities of the lower limbs. The presentation of a clinical case of a patient of the eighth decade of life who presents a giant tumor of the ulcerative abdominal wall and hemorrhage that conditions anemia syndrome and hemorrhagic shock is made, for which an emergency surgical resection is performed. The treatment of leiomyosarcoma consists of surgical removal, however the margins are not clearly defined and regularly require a multidisciplinary team that includes an oncological surgeon and a plastic and reconstructive surgeon. In advanced cases and selected patients, medical treatment with chemotherapy can be granted.